2015
DOI: 10.1590/s0102-865020150120000002
|View full text |Cite
|
Sign up to set email alerts
|

The effects of ankaferd blood stopper and microporous polysaccharide hemospheres on epidural fibrosis in rat laminectomy model

Abstract: The ankaferd blood stopper and microporous polysaccharide hemospheres reduced epidural fibrosis and arachnoideal involvement after laminectomy in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Studies conducted with hemostats or adhesion inhibitors in the literature reported that EF formation was reduced. Ozay et al [20] In the fibrillar group, the IL-6 (1/10³) level was 0.24 ± 0.31, which was significantly lower than that in the control and bipolar groups (p = 0.022). There was no significant difference in the IL-6 level between the control and bipolar groups (p = 0.142).…”
Section: Groupmentioning
confidence: 90%
“…Studies conducted with hemostats or adhesion inhibitors in the literature reported that EF formation was reduced. Ozay et al [20] In the fibrillar group, the IL-6 (1/10³) level was 0.24 ± 0.31, which was significantly lower than that in the control and bipolar groups (p = 0.022). There was no significant difference in the IL-6 level between the control and bipolar groups (p = 0.142).…”
Section: Groupmentioning
confidence: 90%
“…Excessive production of fibrosis at the postoperative epidural bed can cause neural irritation or stretching, and sometimes even mass effects, resulting in radicular symptoms. [44][45][46] Therefore, avoiding or at least minimizing epidural scarring can improve postoperative clinical outcomes. Although it is impossible to completely prevent epidural scarring, efforts made to minimize this phenomenon in laminectomies 47,48 have demonstrated the clinical significance of ligamentum flavum preservation and support the use of endoscopic spine surgeries to minimize epidural scarring through minimizing the extent of laminectomies and ligamentum flavum resection.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no consensus about how many days are needed following the ABS application. The follow-up days are ranged from 7 to 42 days in the reported literature [1,24]. Orhan et al used a 2-week follow-up similar to the present study [25].…”
Section: Ratsmentioning
confidence: 95%